Parallel factor analysis and trilinear partial least squares applied to the UPLC-PDA data array for the quantification of brimonidine tartrate and timolol maleate in an eye drop formulation. Issue 7 (20th April 2016) - Dinç, Erdal; Büker, Eda
ABSTRACT: Simultaneous quantification of brimonidine tartrate (BRI) and timolol maleate (TIM) in an eye drop formulation was performed by applying parallel factor analysis (PARAFAC) and trilinear (three way) partial least squares to the ultra performance liquid chromatography-photodiode array (UPLC-PDA) data array. In PARAFAC and 3 W-PLS1 applications, the co-elution of the related compounds in their chromatograms obtained in the presence of ornidazole as an internal standard (IS) was resolved, and then analyses were performed. On the other hand, a new conventional ultra performance liquid chromatography (UPLC) method was developed after long and tedious studies to get desirable elution of BRI and TIM in a chromatogram using different column and mobile phase system than that of chromatographic conditions of PARAFAC and 3 W-PLS1 applications. The performance and validity of all the proposed methods were confirmed by analyzing independent validation samples consisting of synthetic mixture, intraday and interday samples, and standard addition samples. Analysis results of BRI and TIM in eye drop samples by chemometric PARAFAC and 3 W-PLS1, and conventional UPLC were statistically compared to each other. It was concluded that PARAFAC and 3 W-PLS1 have shortest analysis time and lower cost than the developed conventional UPLC method for the analysis of the related compounds in commercial eye drop preparation with adequate selectivity and sensitivity. GRAPHICAL ABSTRACT: